"Motherhood is like a roller coaster… lots of ups, then downs, something chaotic… "; UK & Israeli women's experiences of motherhood 6-12 months postpartum. (19th October 2020) - Shloim, N.; Lans, O.; Brown, M.; Mckelvie, S.; Cohen, S.; Cahill, J.
ABSTRACT: Background : The motherhood myth has been associated with perceptions of idealised motherhood which makes it difficult for women to express related struggles or distress. This is a second follow-up study focusing on the experiences of mothers from the United Kingdom (UK) and Israel. Methods : Forty-one women were interviewed about their experience of motherhood, body-image, feeding and well-being. Interviews were analysed thematically. Data were driven by the following questions: 1. how do Israeli and UK women experience motherhood 6–12 months postpartum? 2. Are these experiences associated with body satisfaction and well-being? 3. Whether perceptions of motherhood remained stable or changed from early (<6 months) to 12 months postpartum. Results : Three meta-themes were derived from the data relating to motherhood as ideal, good enough or burdened. Such experiences were associated with body acceptance and well-being. The ideal mother was associated with lack of preoccupation with body image whereas the good enough mother aspired to reclaim her mind and her old body. Our findings suggested that the burdened mothers' struggles in relating to motherhood often correlated to a negative body image. Israeli women perceived motherhood as ideal in the early and later postpartum whereas UK mothers continued to relate to their motherhood as ideal 6–12 months postpartum. Conclusions : Perceptions of motherhood varied between Israeli and UK mothers suggesting a diversity positively associated with culture and country. Encouraging mothers to openly share their perceptions of motherhood could lead to improvements in maternal well-being and more positive interactions with the newborn.